2020
DOI: 10.21109/kesmas.v15i3.3301
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Communication between Wives and Husbands: Insights from the 2017 Indonesia Demographic and Health Survey

Abstract: Frequent inter-spousal communication is regarded as an indicator of safe family planning practice. Nevertheless, communication about family planning within couples in Indonesia is still largely unexplored. This study assessed the levels of inter-spousal communication about family planning and its associated determinants, using cross-sectional and nationally representative data from the 2017 Indonesia Demographic and Health Survey (IDHS), from a randomly selected cohort of 8,925 currently-married couples. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
2
0
3
Order By: Relevance
“…This ndings is also consistent with the ndings by Berhane et al, 2011[3] in Angolela Tera District, Amhara Region, Ethiopia, Zakaria and Azim, 2016[26] in Bangladesh and Dodoo et al, 2016 [29] in Kenya in which couples who approve the use of family planning methods were found more likely to communicate about family planning compared to their counterparts who did not approve the use of family planning methods Wives counseling about family planning by health workers were found signi cantly associated with effective spousal family planning communication in this study. This nding is consistent with the ndings by Irawaty et al, 2020 in Indonesia in which wives who discussed family planning with health workers were 2.5 times more likely to communicate about family planning with their spouses compared to their counterparts who did not discuss it with the health workers [30]. Similarly, an interventional study that involved couple counseling about family planning which is conducted in Jordan revealed an increase in spousal communication on family planning, both by women (9.8 percentage points) and by men (10.3 percentage points) [31].…”
Section: Discussionsupporting
confidence: 92%
“…This ndings is also consistent with the ndings by Berhane et al, 2011[3] in Angolela Tera District, Amhara Region, Ethiopia, Zakaria and Azim, 2016[26] in Bangladesh and Dodoo et al, 2016 [29] in Kenya in which couples who approve the use of family planning methods were found more likely to communicate about family planning compared to their counterparts who did not approve the use of family planning methods Wives counseling about family planning by health workers were found signi cantly associated with effective spousal family planning communication in this study. This nding is consistent with the ndings by Irawaty et al, 2020 in Indonesia in which wives who discussed family planning with health workers were 2.5 times more likely to communicate about family planning with their spouses compared to their counterparts who did not discuss it with the health workers [30]. Similarly, an interventional study that involved couple counseling about family planning which is conducted in Jordan revealed an increase in spousal communication on family planning, both by women (9.8 percentage points) and by men (10.3 percentage points) [31].…”
Section: Discussionsupporting
confidence: 92%
“…Inter-spousal communication about family planning matters also reflects the inclusion of men in family planning matters within a family and potentially negotiate reproductive choices together which leads to contraceptive adoption (Shakya et al, 2018). Couples may directly or indirectly influence each other's fertility preferences during the course of their relationship thus it may increase men's probabilities to initiate contraceptive use (Irawaty, Yasin, & Pratomo, 2020;Yeatman & Sennott, 2014) The result of this study also found that those couples whose wives experienced side effect of female contraceptive methods was significantly important in influencing male contraceptive use. Side effects of modern family planning methods, either experienced or anticipated, have been identified as a common reason that women either choose not to start or discontinue contraceptives (Schrumpf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Temuan penelitian ini didukung oleh penelitian Echezona dkk, bahwa kesadaran dan dukungan suami dalam KB sangat terkait dengan keinginan istri untuk menggunakan metode kontrasepsi (Ezeanolue et al, 2015). Sebagian besar, suami terlibat dalam penyuluhan tentang KB, ketika terpapar tentang metode kontrasepsi dari konselor, seperti petugas lapangan KB, dokter, bidan, atau perawat (Irawaty et al, 2020). Selama konseling, pasangan berperan sebagai pendukung dalam menentukan pilihan dalam menggunakan suatu metode kontrasepsi (USAID et al, 2018).…”
Section: Metodologi Penelitianunclassified
“…Komunikasi yang baik antara istri dan suaminya meningkatkan penggunaan metode kontrasepsi modern (Irawaty et al, 2020). Hal ini sesuai dengan penelitian di Angola yang melaporkan bahwa persepsi persetujuan sebagai dukungan pasangan merupakan satu-satunya variabel yang berhubungan kuat dan positif dengan penggunaan kontrasepsi modern (Prata et al, 2019).…”
Section: Metodologi Penelitianunclassified
See 1 more Smart Citation